Borders and the Norman World Frontiers and Boundaries in Medieval Europe. - Armstrong, Dan (Boydell & Brewer, Incorporated, 2023)
Study of the Norman World's borders, frontiers, and boundaries in Europe, shedding fresh light on their nature and extent.